Composición química de aceites de avellanas y nueces producidos en la Norpatagonia - Martin, Dario Miguel; Gallo, Silvia Laura; Fuente, Gaston Eduardo (EEA Valle Inferior, INTA, 2022)
EEA Valle Inferior